Leading at the crossroads: Understanding how identity influences presidential communication for Black community college presidents - McNaughtan, Jon; Hotchkins, Bryan K. (Education Policy Analysis Archives, 2021)
Research on leadership is historically biased, with little consideration for different experiences of leaders of color. In this study, we applied the integrated race and leadership framework (Ospina & Foldy, 2009) and utilized a case study approach focused on the context of institutional communication to analyze the experiences of six Black community college presidents. The study was guided by the overarching question of how racial identity guided what and how presidents communicated. Our findings indicate that these presidents of color viewed their communication through a social justice lens, while also recognizing their responsibility to the institution. Five themes were identified that highlight the strategies and approaches these presidents take when communicating to their campus, including: 1) a consciousness of who is listening, 2) a sense of racial battle fatigue, 3) a focus on local impact, 4) connection and support from the community, and 5) the skill of racial and social adaptation.